Digital Twin - An Innovative Strategy in Healthcare Transformation: An Extensive Review - Subashini, R.; Kanishghasriee, M.; Grace, S.; Sidhiq Fatima, C. Shifa; Sankar, Anupama; Sidhik Fathima, C. Rifa (Journal for Research in Applied Sciences and Biotechnology, 2024)
In an age where the physical and digital worlds progressively intersect, the concept of the digital twin has aroused as a transformative force across various industries. Digital twins are dynamic digital imitations of physical objects; systems are procedures that can be used to simulate, analyse, and optimize their real-world analogue. In the health care field, a lot of work has gone into establishing digital twin of patient and medical devices. The digital twin of the patient is created by digitising the patient’s physical traits and bodily alterations. Real-world utilization of this technology includes accurate maintenance, advanced operational efficiency, and support for well-informed decision-making, all of which are trans-formative. The digital twin revolution is changing how healthcare professionals approach patient care, treatment planning, and facility administration. Digital twins provide instantaneous monitoring, personalized therapy, and predictive analytics by generating dynamic virtual replicas of patients, medical equipment, and healthcare systems. By offering insights on energy use, material consumption, and other vital variables, digital twin facilitates improved resource management and boosts businesses by cutting costs and waste. Digital twins are positioned to play a vital role in modern healthcare, inciting innovation and efficiency throughout the sector as technology advances. We focused on applications and development of digital twin in healthcare sector by analyzing a large number of studies from distinct medical sector, the effectiveness of digital twin in imaging studies and diagnosis, cancer, cardiology, neurology has been discussed in this review.